(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Microbiological processes occur in the soil around the roots of land plants. This dynamic area, where plants and microorganisms interact, is crucial for the health and productivity of these plants. This study was aimed at isolating and molecularly identifying bacteria associated with the soil surrounding the root of an orange tree growing in the University of Ilorin, Nigeria to be able to know their roles, whether beneficial or harmful. Securing the soil is a way of having a food-secured world. Soil samples were collected at four different points from an orange tree trunk into separately labeled Ziploc bags using a separate sterile hand trowel for each collection. The labeled ziploc bags were brought to the University of Ilorin’s Biology Laboratory for physicochemical analysis of the soil sample and isolation of bacteria using serial dilution method. Results of the physicochemical assessment of the bulked sample indicated that it is a sandy-loam soil with pH value of 6.7 (slightly neutral). Four bacterial species, i.e. Bacillus cereus, Lysinibacillusmacroides, Leucobacterkomogatae, and Alcaligenesfaecalis were isolated and identified molecularly. According to existing literature, the four bacterial species identified in this study are known for their abilities to enhance plant development and solubilize phosphorus, which are crucial for improving supply of nutrient.